Insights into the bacterial synthesis of metal nanoparticles - Campaña, Ana Lucía; Saragliadis, Athanasios; Mikheenko, Pavlo; Linke, Dirk (Frontiers in Nanotechnology, 2023)
Metal nanoparticles have attracted considerable attention due to their astounding potential for a wide range of commercial applications. From targeted drug delivery and antimicrobial agents to electronics, metal nanoparticles seem to have immeasurable prospects in all areas of science. However, modern industrial production frequently involves complex procedures, large amounts of energy, utilizes strong chemical solvents, or produces hazardous waste. Biological synthesis has been proposed as an alternative for simpler, inexpensive, and more eco-friendly metal nanoparticle production. Microorganisms possess multiple mechanisms to transport, regulate and bind metal ions that may result in the biosynthesis of nanoparticles. They can synthesize even complex bimetallic nanoparticles, which are difficult to produce with normal chemical and physical processes. A better understanding of bacteria-metal interactions might thus pave the way for a wide array of industrial applications. This review will summarize the current methods for metal nanoparticle synthesis, with a focus on the microbial (bio)synthesis of nanoparticles. We will describe the general mechanisms of bacteria-metal ion interactions, including cellular uptake and the subsequent reduction into nanoparticles. Protocols for the production of metal-based nanoparticles of relevant elements with different bacterial strains are compiled and the current challenges in bacterial synthesis of metal nanoparticles in the industry are discussed.